From Information Management to Information Visualization - Karami, Mahtab; Safdari, Reza (Applied Clinical Informatics, 2016)
The development and implementation of a dashboard of medical imaging department (MID) performance indicators.Several articles discussing performance measures of imaging departments were searched for this study. All the related measures were extracted. Then, a panel of imaging experts were asked to rate these measures with an open ended question to seek further potential indicators. A second round was performed to confirm the performance rating. The indicators and their ratings were then reviewed by an executive panel. Based on the final panel’s rating, a list of indicators to be used was developed. A team of information technology consultants were asked to determine a set of user interface requirements for the building of the dashboard. In the first round, based on the panel’s rating, a list of main features or requirements to be used was determined. Next, Qlikview was utilized to implement the dashboard to visualize a set of selected KPI metrics. Finally, an evaluation of the dashboard was performed.92 MID indicators were identified. On top of this, 53 main user interface requirements to build of the prototype of dashboard were determined. Then, the project team successfully implemented a prototype of radiology management dashboards into study site. The visual display that was designed was rated highly by users.To develop a dashboard, management of information is essential. It is recommended that a quality map be designed for the MID. It can be used to specify the sequence of activities, their related indicators and required data for calculating these indicators. To achieve both an effective dashboard and a comprehensive view of operations, it is necessary to design a data warehouse for gathering data from a variety of systems. Utilizing interoperability standards for exchanging data among different systems can be also effective in this regard.
Keywords: Medical imaging; radiology; information; management; dashboard; visualization; performance indicators